Health Information Behaviors of Older Adults for Diabetes Prevention in Pattani Province - Kewsuwun, Nawapon (Journal of Information Science Research and Practice, 2022)
Purpose: This study intends to explore health information behaviors and problems concerning health information seeking and use for diabetes prevention of the elderly in the province Methodology: This survey research employs questionnaires to collect data form 240 sixty-year old and older elderly purposively selected from 12 districts of Pattani Province from June to September of 2021, and the collected data are statistically analyzed. Findings: The study results show that 1) the health information behaviors for preventing diabetes of the elderly in Pattani Province is found to be at the high level (Ⴟ = 4.08). Also, in the analysis of each aspect of the information behaviors, health information seeking gains the highest average scores (Ⴟ = 4.11), followed by information use (Ⴟ = 4.08), and information needs (Ⴟ = 4.06) respectively. With regard to the information sources frequently used by the participants are institutional sources, such as libraries, and community learning facilities (Ⴟ = 4.23); and 2) the problems in seeking and using health information for diabetes prevention of the elderly is found to be as high as Ⴟ = 4.00 while the seeking aspect is reportedly higher than the using one at Ⴟ = 4.02 and Ⴟ = 3.98. Applications of this study: This study can benefit information service institutions, such as public libraries, community learning centers and school and academic libraries, including those agencies responsible for producing health information and providing information services suitable for users’ needs to design their information services to better serve the elderly in Pattani province based on their information behavior. In addition, public health agencies and sub-district health promoting hospitals can apply the recommendations from this study in their health policy formulation and health strategic planning for the elderly health improvement and wellbeing.